External validation study of the 2014 European Society of Cardiology Guidelines in relation to 2020 ACC/AHA guidelines on sudden cardiac death prevention in hypertrophic cardiomyopathy. (19th May 2022) - Frochaux, A; Maurizi, N; Porretta, AP; Nana Davies, S; Pascale, P; Janreaud, X; Pruvot, E; Monney, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Strategies for reliable selection of high-risk hypertrophic cardiomyopathy (HCM) patients for prevention of sudden cardiac death (SCD) with implantable cardioverter-defibrillators (ICDs) are still debated. Purpose: Assess the sensitivity of sudden death risk strategies (2014 ESC SCD 5-year risk score and 2020 ACC/AHA risk factor strategy) in predicting lethal arrhythmic events (LAE), appropriate ICD shocks, SCD or out of hospital cardiac arrest among a cohort of HCM patients Methods: Sixty-five patients (42±17 y) with a clinical diagnosis of HCM were enrolled in our institution from 1990 to 2021. Among them, 28 patients (43%) underwent a genetic test and a pathogenic/likely pathogenic sarcomeric variant was detected in 23 cases (82%). Patients were managed according to the best available treatment strategy for HCM in the different clinical eras. Results: Of the 65 patients, 28 cases (43%) received an ICD, including 23 for primary and 5 for secondary prevention. During a follow-up period of 15 years (median, 15 [6, 21], range 1 to 33 years, 1014 patients/year), a total of 10 LAE were observed (0.98%/year). According to ESC SCD 5-year Risk Score, 7 (10%) were at high risk, 14 (22%) at intermediate to high risk, and 44 (68%) at low risk. Median SCD 5-year risk score of 3.5% ± 2.1. ACC/AHA risk factors categorized patients as 35 (54%) at high risk, 24 (37%) at intermediate to high risk, and 6 (9%) at low risk. A total of 4 (2.8%) patients experiencing SCD events were misclassified as low-risk patients by the ESC SCD Risk Score, whereas none by the ACC/AHA model. Of the 7 patients categorized as high risk by the ESC SCD Risk Score, 2 (29%) experienced a LAE, whereas of the 35 patients at high risk by the ACC/AHA, 9 (26%) suffered a LAE. No difference in the area under the curve was showed for the 2020 ACC/AHA SCD risk stratification strategies with respect to 2014 ESC SCD 5-year-risk score (0.72; 95% CI 0.60–0.83, 0.66; 95% CI 0.49–0.84, p =0.55). Conclusions: In this HCM cohort followed up over an extended period of more than 15 years, LAE remained relatively low (0.98%/year). SCD risk stratification recommended by the 2014 ESC SCD 5 year risk score did not showed a better discrimination than that of 2020 ACC/AHA stratifications, despite the latter proved to be more sensible in the identification of the low risk patients. More than half of our cohort was classified with a recommendation by the 2020 ACC/AHA for an ICD implantation. A larger multicenter, independent, and prospective study with long-term follow-up is warranted to better elucidate these results.